The Influence of Leisure Activity Types and Involvement Levels on Leisure Benefits in Older Adults - Li, Jintian; Zeng, Baogen; Li, Peiyan (Frontiers in Public Health, 2021)
Purpose: To explore the types of leisure activities, the degree of activity involvement, and the relationship between leisure benefits in older adults in cities and towns in northern Guangdong, China, to provide valuable references for formulating related policies on the leisure industry for relevant governing bodies and for gaining the optimal benefits for industry business people and leisure enthusiasts. Methods: After searching for a large amount of literature and expert consultations, a questionnaire on the leisure involvement and leisure benefits scale was constructed. Participants aged 60 years or older were recruited as the survey population. By using SPSS statistics 21.0, the raw and processed data in this study were analyzed and interpreted. Results: 1) The approach that the leisure involvement levels were divided into subjective and objective involvement levels to predict leisure benefits was more comprehensive and reliable than uni-level prediction. Among them, the overall leisure involvement level had a significant positive effect on the leisure benefits of leisure participants; the performance of the subjective involvement level to enhance the leisure benefits comprehensively surpassed the objective involvement level; 2) The effect of leisure involvement levels on leisure benefits was affected by the type of leisure, which was manifested as physiological and psychological leisure pleasure, The degree of leisure involvement had an inverted U-shaped relationship with its emotional leisure benefits. For individuals with physiological hedonistic leisure, the degree of leisure involvement had an inverted U-shaped relationship with its emotional, social, and self-realized leisure interests; 3) For individuals with psychological leisure, the degree of leisure involvement was positively U-shaped with its social and self-affirmed leisure benefits. However, this finding needs to be confirmed by further research. Conclusion: There are two types of linear and curvilinear relationships between the degree of leisure involvement and leisure benefits, which makes the connection between leisure involvement and leisure benefits deviate from the linearity in a particular situation and present an inverted U-shaped or positive U-shaped relationship, which shows when the individuals are under- or over-volume leisure activities involvement, they will not create excellent leisure benefits.